Targeting the Genome‐Stability Hub Ctf4 by Stapled‐Peptide Design. Issue 42 (7th September 2017) - Wu, Yuteng; Villa, Fabrizio; Maman, Joseph; Lau, Yu Heng; Dobnikar, Lina; Simon, Aline C.; Labib, Karim; Spring, David R.; Pellegrini, Luca
Abstract: The exploitation of synthetic lethality by small‐molecule targeting of pathways that maintain genomic stability is an attractive chemotherapeutic approach. The Ctf4/AND‐1 protein hub, which links DNA replication, repair, and chromosome segregation, represents a novel target for the synthetic lethality approach. Herein, we report the design, optimization, and validation of double‐click stapled peptides encoding the Ctf4‐interacting peptide (CIP) of the replicative helicase subunit Sld5. By screening stapling positions in the Sld5 CIP, we identified an unorthodox i, i+6 stapled peptide with improved, submicromolar binding to Ctf4. The mode of interaction with Ctf4 was confirmed by a crystal structure of the stapled Sld5 peptide bound to Ctf4. The stapled Sld5 peptide was able to displace the Ctf4 partner DNA polymerase α from the replisome in yeast extracts. Our study provides proof‐of‐principle evidence for the development of small‐molecule inhibitors of the human CTF4 orthologue AND‐1. Abstract : Interfering with the replisome : The replisome hub protein Ctf4 represents an attractive potential target for developing cancer therapeutics. The development of stapled peptides that disrupt the interaction of Ctf4 with its client proteins in the replisome provides proof‐of‐principle evidence of how this can be achieved. CIP=Ctf4‐interacting peptide.